WATER LEVEL VARIATIONS FOR EGG HATCHABILITY AND LARVAL SURVIVAL OF KELABAU FISH (Osteochilus melanopleura Blkr) - Rukmini, Rukmini (TROPICAL WETLAND JOURNAL, 2016)
The purposes of this study were to observe and analyze the water level variations of the culture media that were optimal for egg hatchability and larval survival of kelabau fish kept in aquarium. This study was conducted in the Freshwater Aquaculture Development Centre (FADC) Banjar Regency in August 2015. The method used in this study was experimental, using a completely randomized design with 3 treatments (A = water level of 15 cm/aquarium), (B = water level of 25 cm/aquarium), (C = water level of 35 cm/aquarium) and 3 replications. The parameters measured in this study were the egg hatchability, survival rate, relative growth rate, and water quality (temperature, pH, DO, Ammonia). Data were analyzed by Anova and the differences between treatments were tested with Duncan test. The results showed that the water level very significantly affected the egg hatchability with the highest value in B (38.29%) followed by C (31.83%) and A (14.04%). The highest survival rate was in C (79.73%) followed by B (65.10%) and A (21.83%). The relative growth rate had not significant effect with the average results between all treatments (104.92 – 117.27%). The water quality of the culture media was still good to support the growth and survival of fish.